PENERAPAN TEKNOLOGI BLOCKCHAIN DALAM MANAJEMEN LOGISTIK PERTAHANAN - Maharani, Tiara Devi; Sarjito, Aris; Marnani, Christine Sri (JAMI: Jurnal Ahli Muda Indonesia, 2023)
Logistics management plays a pivotal role in ensuring the success of military operations within the realm of defense. With the primary goals of enhancing timeliness, transparency, and the overall security of defense asset management, blockchain technology has emerged as an intriguing solution. This educational article endeavors to delve into the concept and utilization of blockchain technology in the logistics management of defense, while also shedding light on the advantages and constraints associated with its implementation. This study adopts a literature review methodology to unravel the intricacies of applying blockchain technology in defense logistics. The findings reveal a multitude of challenges when implementing blockchain technology, including issues related to human resources, technological readiness, regulatory ambiguities, the customization of blockchain systems for strategic defense logistics applications, and the preservation of data integrity. The adoption and implementation of blockchain technology within the field of defense logistics is not a direct, one-size-fits-all process. Instead, tailored adaptations are made to address the unique demands of defense logistics, which often necessitate restricted access for specific stakeholders due to the sensitive nature of the sector. In conclusion, this research underscores the significant potential of blockchain technology in the realm of defense logistics. However, it emphasizes the necessity for further in-depth research and meticulous adaptation to ensure a seamless integration of this technology into the complex landscape of defense logistics.